Character Building Management Through Civic Education on Awareness of Compliance with Regulations at UIN SU Medan - Nasution, Toni (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The Civic Education course plays an important role in shaping the character of university students. However, many students still lack awareness of the values of nationalism and patriotism. This is reflected in their lack of respect for national symbols, such as reluctance to participate in flag ceremonies or a lack of understanding of the importance of maintaining national unity. To address this issue, collaboration among various parties is required. This study employs a qualitative method with a case study approach, conducting interviews with lecturers, students, and staff at UIN SU Medan who participate in the learning process in the classroom. This approach aims to gain a deep understanding of the phenomenon within a real-world context. Applicable learning methods, relevant training programs, and discussions tailored to students' needs are required to increase awareness of the importance of obeying regulations. Civic Education also faces several challenges, such as poor communication between units, monotonous learning methods, and low student motivation. As a solution, innovative strategies such as the use of creative learning methods are needed. At UIN SU Medan, Civic Education is able to encourage students to be more disciplined and obedient to rules. Methods such as project-based learning, group discussions, and seminars have proven to help students understand the importance of order. One of the lecturers' strategies is to set specific rules in the course and explain them in detail at the beginning so that students get used to obeying them.